Start-Up culture in Latin America - Paz Chavez, Jose Miguel; Pichanič, Mikuláš, 1942-; Říha, David; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The overall goal of this thesis was to assess the markets in Latin America and to provide an overview of what is to be encountered for any person wishing to start a new business in the region. In order to do so, the example of the most important Startup in recent times was used, the Hugo App. With this, it gives an idea that it can all be possible with some effort and with an excellent overview of the market about to be entered.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses